2020
DOI: 10.3390/ma13204653
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Silver Nanostructures and Graphene Oxide Applied as Surface Modification of TiO2 in Photocatalytic Transformations of Rhodamine B under UV and Vis Irradiation

Abstract: This work is focused on photocatalytic properties of titanium dioxide thin coatings modified with silver nanostructures (AgNSs) and graphene oxide (GO) sheets which were analyzed in processes of chemical transformations of rhodamine B (RhB) under ultraviolet (UV) or visible light (Vis) irradiation, respectively. UV-Vis spectroscopy was applied to analyze the changes in the RhB spectrum during photocatalytic processes, revealing decolorization of RhB solution under UV irradiation while the same process coexisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 63 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…On the other hand, the photodegradation process went mainly through the N-de-ethylation process under visible light irradiation which mainly has a characteristic hypsochromic shift of maximum absorbance of RhB but no decrease in the maximum absorbance. The differences between two RhB degradation pathways under different light exposure conditions are directly related to the photogenerated radicals which are • O 2 – responsible for the N-de-ethylation processes and • OH responsible for the direct cleavage. , Thus, the radicals produced during the process were examined by using the well-known radical scavenger of TA to better understand the reason for the differences in RhB spectra. TA is a convenient chemical probe molecule that reacts with • OH radicals in the medium and consequently transforms into fluorescent 2-hydroxy terephthalic acid (2-HTA) (Figure S7a).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the photodegradation process went mainly through the N-de-ethylation process under visible light irradiation which mainly has a characteristic hypsochromic shift of maximum absorbance of RhB but no decrease in the maximum absorbance. The differences between two RhB degradation pathways under different light exposure conditions are directly related to the photogenerated radicals which are • O 2 – responsible for the N-de-ethylation processes and • OH responsible for the direct cleavage. , Thus, the radicals produced during the process were examined by using the well-known radical scavenger of TA to better understand the reason for the differences in RhB spectra. TA is a convenient chemical probe molecule that reacts with • OH radicals in the medium and consequently transforms into fluorescent 2-hydroxy terephthalic acid (2-HTA) (Figure S7a).…”
Section: Resultsmentioning
confidence: 99%
“…A similar study of the SEM image showed the morphology of the obtained TiO 2 -AgNS photocatalyst; TiO 2 NPs are visible as white objects with a quasi-spherical shape. The average particle size estimated for Ag NSs was 18 ± 3 nm [ 25 ]. The shape of the titanium can be influenced by the graphene oxides, this is maybe due to the structure of graphene that differs from the titanium since graphene structure is said to be a two-dimensional plate-like shape, whereas the titanium NPs exhibit sphere shape when both the metals where brought into the combination it may exert in a quasi-spherical shape structure [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Graphene and titanium dioxide are introduced as coating materials. By suppressing the productivity of reactive oxygen species of bacterial pathogens through photocatalytic activity, antibacterial activities can be performed [ 25 ]. The combination of the titanium and graphene oxide provides a synergic effect by reducing the surface wettability by increasing the surface roughness based on the water contact angle by increasing the concentration of the nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Shuya Xu reported that Ag/Ba-TiO 3 showed an excellent photocatalytic property and degraded 83% RhB in 75 min, which is 20% more than the sole photocatalyst TiO 3 [15]. Similarly, Kaja Spilarewicz modified the surface of TiO 2 with Ag and graphene nanostructures and reported the enhanced photocatalytic performance by degrading 93% RhB in 300 min [16]. Yutong Liu and his team reported the excellent photocatalytic performance of Ag-modified ZnO and recorded 100% degradation of MB in 40 min [17].…”
Section: Introductionmentioning
confidence: 98%